Gender, property rights, and natural resources - Meinzen-Dick, Ruth S.; Brown, Lynn R.; Feldstein, Hilary Sims; Quisumbing, Agnes R. (Elsevier, 1997)
Attention to gender differences in property rights can improve the outcomes of natural resource management policies and projects in terms of efficiency, environmental sustainability, equity, and empowerment of resource users. Although it is impossible to generalize across cultures and resources, it is important to identify the nature of rights to land, trees, and water held by women and men, and how they are acquired and transmitted from one user to another. The paper particularly examines how the shift from customary tenure systems to private property--in land, trees, and water--has affected women, the effect of gender differences in property on collective action, and the implications for policy formulation and implementation.